If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + -3 = 15 Reorder the terms: -3 + 6m = 15 Solving -3 + 6m = 15 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 6m = 15 + 3 Combine like terms: -3 + 3 = 0 0 + 6m = 15 + 3 6m = 15 + 3 Combine like terms: 15 + 3 = 18 6m = 18 Divide each side by '6'. m = 3 Simplifying m = 3
| (s+3ux)*(2s+3ux)= | | 2x-y=3d | | 20x^2-28x-3= | | 6z=48 | | -4x-2=-5 | | (7x-2y)*(x+y)= | | 8h=-88 | | (2x^2+3y)*(2x^2-2y)= | | -12v=-36 | | (6s+8nx^2)*(s-nx^2)= | | 6=5+6 | | (6s+8mx^2)*(s-nx^2)= | | 6x(6x)+2=98 | | 6x(6x)-2=98 | | (5a+6b^2)*(a-b^2)= | | 0=-16x^2+64x+128 | | x+4(x+2)=46 | | 7x+3=4x+11 | | (4x-3tv^2)*(x+2tv^2)= | | (2w-9)(w+3)=0 | | 0.60x+.05(10-x)=.10(60) | | 5x+883x=3-2x-5 | | 0.60+.05(10-x)=.10(60) | | 11x-23=8x+13 | | 3r^2+23r+40= | | -8=8x | | 0=3(1-2x)-5(3-x) | | t^2+11t+30= | | y(3-2y)-3(2m-1)=9 | | 5x+2+8x-7=180 | | y(3-2y)-3(sm-1)=9 | | 20=-0.66x |